Isolasi dan Karakterisasi Senyawa Steroid dari Ekstrak Aseton Daun Faloak (Sterculia quadrifida R.Br) - Burhanuddin Taebe; Imrawati Imrawati; Cindy Nuradzani Rachman (Jurnal Farmasi dan Ilmu Pengobatan, 2018)
Faloak leaves (Sterculia qudrifida R.Br) has been used by Aborigine ethnic to treat insect bites, cuts, arrowheads, stinging wounds and injury. This study was aimed to isolate and characterize the steroid compounds from the acetone extract of faloak leaves. Extraction by maceration method use acetone as solvent than acetone extract was partitioned again with n-hexane and ethyl acetate. The steroids positive fraction was separated using preparative thin layer chromatography and thin layer chromatography 2 dimensions for testing the purity. The isolate was characterized using FT-IR. The results of spectroscopic analysis FTIR show that isolates suspected were steroids compounds with functional group C=O, C- O, C=C, C-C, and C-H.